Understanding the Health-related Quality of Life of People Living with HIV Based on Sexual Orientation - Sitorus, Rico Januar; Antara, Nyoman Yudi; Sangalang, Reymart; Panjaitan, Merry Natalia; Fauk, Nelsensius Klau (Kesmas, 2023)
Human immunodeficiency virus (HIV) infection has detrimental impacts on the lives of different population groups living with HIV, including men who have sex with men (MSM). Using the World Health Organization Quality of Life questionnaire, this study aimed to assess the health-related quality of life of men living with HIV with different sexual orientations and to determine the dominant influential factors. This cross-sectional study involved 206 men living with HIV. They were recruited from the Sriwijaya Plus Foundation and a medical facility that provided antiretroviral therapy. The data were analyzed using Chi-square and binomial logistic regression. The analysis showed that the percentage of MSM patients was greater than that of non-MSM patients, accounting for 68.9% of the total population. The multivariate logistic regression revealed that the most dominant influential factor was depression status (PR = 5.417; 95% CI = 2.473–11.876), with the majority of the depressed patients being 5.417 times more at risk of a lower quality of life compared to others. These findings suggest that depression can lead to a low quality of life among HIV patients.